If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1a + 3b = 6 Solving 1a + 3b = 6 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. 1a + 3b + -3b = 6 + -3b Combine like terms: 3b + -3b = 0 1a + 0 = 6 + -3b 1a = 6 + -3b Divide each side by '1'. a = 6 + -3b Simplifying a = 6 + -3b
| 6s+-8=18 | | (2x+4)(3x-3)=0 | | x-2.4=5.6 | | 3x^3+87x^2+162x=0 | | 5x+1-18= | | (7x+15)+(x+5)=180 | | .25(8-6x+12)= | | 15a^2-8=29a+9 | | 2x^3-21x^2+34x=0 | | 8x^3-3x^2-32x+12=0 | | 10+3x+2x=-45 | | 9+2y=y | | 9(x-1)=6(x+5) | | (3+w)w=w(7-w) | | 5j-j=12 | | x^2-50x+100=8400 | | 6x^3+26x^2-76x=0 | | 9-(w+4)=-10 | | 2x-6-2(2x+8)3=4x+1 | | 3.5x=9 | | .1x-.9x^2=0 | | X^2+24x=172 | | 8=4+4 | | -5(5p+2)-49=3(3p+3) | | 8x^3-3x^2=32x-12 | | 5f-15=2f-3 | | d/dx(9x/8) | | (x-1)(5x+2)=-13(x-1) | | 3x/4-x=x/10-5/2 | | 4x-3+43=180 | | 28p^2-108p-14=2 | | -4x^3-40x^2-64x=0 |